Oral, Neck and Orofacial Infections and Non -Bacterial Infection – A Review - ELANGKOVAN, DENESH RAJ; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2020)
This study aimed to determine the advancement of the medical field to cure diseases using drug and therapeutic agents. Therapeutic agents used in advancement are important in the combat of diseases. Multitargeted combination therapy has also been targeted by many clinicians due to the synergism interaction existing between many antifungal agents proven by in vitro studies. Bacterial infection which is commonly caused in the oral, neck and orofacial region. The knowledge of current concepts of orofacial infections, causative agents, their classification and clinical manifestations and a basis for management is essential for providing appropriate dental care to Patients